SASTRA TEMBANG PADA KONTEKSTUAL ADEGAN DAMARWULAN SEBAGAI PENGUASA MAJAPAHIT DALAM TARI LANGENDRIYAN - Sutarno Haryono (Institut Seni Indonesia Surakarta, 2014)
The presence of dance is generally not a construction whose elements can be analyzed butrather a unified or cohesive whole (gestalt). Thus, presentational symbols rather than discursivesymbols appear. Presentational symbols refer to the meaning that is hidden behind the meaningthat is immediately visible, or reveal a level of meaning that is presupposed within the literalmeaning. Of course, interpreting an art which contains several different elements, such as the artof dance, is highly complex since it is constructed of elements that are bound together and cannotbe separated from each other.Keywords: Analysis, Contextual,Macapat, Dance Movements.